Oral nano-formulation improves pancreatic islets dysfunction via lymphatic transport for antidiabetic treatment - Lin Hou; Xueyuan Peng; Ruiting Wang; Yifei Wang; Hong Li; Huijuan Zhang; Yun Zhang; Zhenzhong Zhang (Elsevier, 2023)
Type 2 diabetes mellitus (T2DM) therapy is facing the challenges of long-term medication and gradual destruction of pancreatic islet β-cells. Therefore, it is timely to develop oral prolonged action formulations to improve compliance, while restoring β-cells survival and function. Herein, we designed a simple nanoparticle with enhanced oral absorption and pancreas accumulation property, which combined apical sodium-dependent bile acid transporter-mediated intestinal uptake and lymphatic transportation. In this system, taurocholic acid (TCA) modified poly(lactic-co-glycolic acid) (PLGA) was employed to achieve pancreas location, hydroxychloroquine (HCQ) was loaded to execute therapeutic efficacy, and 1,2-dilauroyl-sn-glycero-3-phosphocholine (DLPC) was introduced as stabilizer together with synergist (PLGA-TCA/DLPC/HCQ). In vitro and in vivo results have proven that PLGA-TCA/DLPC/HCQ reversed the pancreatic islets damage and dysfunction, thus impeding hyperglycemia progression and restoring systemic glucose homeostasis via only once administration every day. In terms of mechanism PLGA-TCA/DLPC/HCQ ameliorated oxidative stress, remodeled the inflammatory pancreas microenvironment, and activated PI3K/AKT signaling pathway without obvious toxicity. This strategy not only provides an oral delivery platform for increasing absorption and pancreas targetability but also opens a new avenue for thorough T2DM treatment.